Clinical outcomes of Preimplantation genetic testing (PGT) application in couples with chromosomal inversion, a study in the Chinese Han population - Yuhan Shao; Jing Li; Juanjuan Lu; Hongchang Li; Yueting Zhu; Wenjie Jiang; Junhao Yan (BMC, 2020)
Abstract Background Chromosomal inversion was considered to have adverse effects on pregnancy outcomes through abnormal gametogenesis. The purpose of this retrospective study was to investigate whether preimplantation genetic testing (PGT) improves pregnancy outcomes for couples with chromosomal inversion. Methods A total of 188 cycles from 165 couples with one chromosomal inversion carrier were divided into two groups: PGT (136 cycles, 125 couples) and non-PGT (52 cycles, 50 couples). Biochemical pregnancy, clinical pregnancy, ongoing pregnancy, miscarriage and live birth rates of their first transfer cycles, as well as cumulative live birth rates of each cycle and euploidy rates, were analyzed. Results There were no statistically significant differences in the pregnancy outcomes between the two groups. The euploidy rate of pericentric inversion carriers was not higher than that of paracentric inversion carriers in PGT group (60.71% vs 50.54%, P = 0.073). Similarly, the euploid rate of male carriers was not higher than that of female carriers (61.2% vs 56.1%, P = 0.256). Conclusions Due to limitation of retrospective study and small sample size, our current data showed that PGT cannot provide prominent benefits for inversion carriers in the Chinese Han population. Further prospective randomized controlled trials are needed to evaluate the effects of PGT.